Building crack characterization using an hybrid approach - Salami, Abdulazeez F.; Aibinu, Abiodun Musa; Shafie, Amir Akramin; Salami, Momoh Jimoh Emiyoka; Bamgbopa, Ibrahim A.; Lawal, Wahab Adetunji (2009)
Crack can easily be seen on many buildings and along major roads in developing and developed countries. These cracks come in various shapes, sizes and orientation. The main objective of this work is to apply digital signal and image processing techniques to crack detection and analysis so as to establish a grading system for building and road cracks automation system. An hybrid technique using Neural network and Image analysis in determining the size, width, length, orientation and dimension of crack is hereby proposed. Preliminary result obtained shows that this technique will solve the problem of manual screening and analysis of cracks on roads and buildings, hence an improvement in the efficiency of this task and a good step in automation of the process.